2016
DOI: 10.1007/s00167-016-4364-y
|View full text |Cite
|
Sign up to set email alerts
|

Youth baseball players with elbow and shoulder pain have both low back and knee pain: a cross-sectional study

Abstract: Objectives: Serious arm injuries in youth baseball players have been increasing. Though a breakage in the kinetic chain could affect arm injuries, an association between arm injuries and insufficient support of the trunk and lower extremities have not been well understood. The purpose of this study was to investigate the association of low back and knee pain with elbow and/or shoulder complaints among youth baseball players. Methods: Study participants were mostly school-aged athletes belonging to Junior Sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
1
27
0
1
Order By: Relevance
“…This result is consistent with a previous study that showed significant associations of pain in the low back or knee with elbow and shoulder pain in young baseball players (Sekiguchi et al 2016). Possible explanations for these associations are as follows.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is consistent with a previous study that showed significant associations of pain in the low back or knee with elbow and shoulder pain in young baseball players (Sekiguchi et al 2016). Possible explanations for these associations are as follows.…”
Section: Discussionsupporting
confidence: 93%
“…School-aged athletes belonging to the Miyagi Amateur Sports Association, established with the aim of promoting youth health through various sports, participated in the study (Sekiguchi et al 2016). This organization held contact information for 25,469 registered athletes and their parents.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because energy derived from the lower extremity passes through the trunk to the upper extremity in throwing motion, a break in such a kinetic chain could lead to upper extremity injuries. In fact, both lower back and knee pains are signifi cantly associated with the elbow and/or shoulder pain in youth baseball players (Sekiguchi et al 2018). These involved body parts in these pains are linked and work together during running, jumping, and throwing (Nadler et al 1998).…”
Section: Introductionmentioning
confidence: 99%